Effect of One-Stage versus Two-Stage Palatoplasty on Hypernasality and Fistula Formation in Children with Complete Unilateral Cleft Lip and Palate: A Randomized Controlled Trial. Issue 1 (July 2018) - Reddy, Rajgopal R.; Gosla Reddy, Srinivas; Chilakalapudi, Anusha; Kokali, Swapnika; Bronkhorst, Ewald M.; Kummer, Ann W.; Bergé, Stefaan J.; Kuijpers-Jagtman, Anne Marie
Abstract : Background: Is one-stage or two-stage palatoplasty more effective for preventing fistula formation and hypernasality in patients with complete unilateral cleft lip and palate? Methods: This parallel blocked randomized controlled trial included 100 patients with nonsyndromic complete unilateral cleft lip and palate with a repaired cleft lip, divided into two equal groups. Group A had one-stage palatoplasty patients at age 12 to 13 months while group B had two-stage palatoplasty patients with soft palatoplasty at age 12 to 13 months and hard palatoplasty at age 24 to 25 months. Presence of a fistula was tested clinically at 3 years and speech was tested using nasometry and perceptual analyses at 6 years. Group C consisted of noncleft controls ( n = 20, age 6 years) for speech using nasometry. Fistula rates, hypernasality ratings, and nasalance scores were compared between groups A and B. Nasometry recordings of groups A and B were compared with control group C. Results: There was no difference in fistula rates between groups A and B ( p = 0.409; 95 percent CI, 0.365 to 11.9). Mean nasalance scores of group A showed higher nasalance than group B ( p = 0.006; 95 percent CI, 1.16 to 6.53). Perceptual analysis showed no difference between groups A and B ( p = 0.837 and p = 1.000). Group A showed higher mean nasalance than group C ( p = 0.837 and p = 1.000), whereas group B showed no difference ( p = 0.088; 95 percent CI, −0.14 to 2.02). Conclusions: There was no difference in fistula rates between groups. Nasalance was slightly higher in patients in the one-stage palatoplasty group than two-stage palatoplasty group, but the difference was not clinically significant. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.